Integrating ride-sourcing with electric vehicle charging under mixed fleets and differentiated services. (January 2023) - Cai, Zeen; Mo, Dong; Geng, Maosi; Tang, Wei; Chen, Xiqun Michael
Highlights: Propose a novel nested two-sided market model with integrated ride-sourcing and electric vehicle (EV) charging services. Consider differentiated charging pricing and priority of ride-sourcing and private EV drivers. Reveal mathematical properties of EV drivers' charging behavior, passengers' mode choices, and platform's decisions. Derive optimal states of profit maximization, social optimum, and Pareto optimality. Analyze potential impact of introducing integrated services with two strategies. Gain managerial insights into platform operations and government regulation. Abstract: This paper proposes a novel nested two-sided market framework to investigate integrated ride-sourcing (RS) and electric vehicle (EV) charging services considering mixed electric and gasoline vehicles (GVs). In the proposed integrated scheme, a monopoly RS platform builds or purchases charging piles to provide RS and private EV drivers with additional differentiated services (i.e., different charging prices and priority) besides public charging piles. Both RS and private drivers with different charging pile ownership are considered. The complex endogenous correlations between RS and charging services are formulated. The mathematical properties of drivers' charging behavior, passengers' mode choices, and platform's operation strategies are analytically derived, which is closely related to the differentiated priority of drivers. The conditions for judging the profitability of the RS and charging business under profit maximization strategies are obtained. We examine and compare the potential impact of introducing integrated services with two strategies and identify the sufficient conditions to boost total profit by providing the integrated services. It is rigorously proved that the integrated services benefit passengers and specific driver groups, while it may be harmful to the environment under a high RS electrification level. The Pareto-efficient frontiers indicate that the charging price for RS drivers in the social optimum regime is higher than that in the profit maximization regime. The analytical results gain managerial insights into platform operations and government regulation of integrated RS and charging services in the RS market under mixed fleets of EVs and GVs.